Faktor yang Mempengaruhi Produktivitas Kerja Perawat di Rs. Bhayangkara Tk. III Manado - Marani, Ivonella; Pondaag, Ferlan; Ahmad, Musfirah (Program Studi Ilmu Keperawatan Fakultas Kedokteran Universitas Sam Ratulangi, 2025)
Background Nurses have a very important role in improving the quality of hospital services. Nurse work productivity affects the quality of hospital services. Previous research concluded that nurse performance indicators greatly influence the quality of hospital services. Objective To analyze the factors related to the work productivity of nurses in hospitals. Bhayangkara Tk III Manado. Methods This research is a quantitative study with a cross-sectional design which was conducted in April 2023 at Bhayangkara Hospital Manado North Karombasan, Wanea District, Manado City, North Sulawesi. Collecting data using a research questionnaire to 70 respondents who have been tested for validity and reliability. Statistical test using univariate and bivariate analysis. Results Most of the nurses had high motivation, namely 77.1%, the majority of nurses had low income levels, namely 92.9%, most of the nurses had a good perception of the work environment, namely 81.4%. There is no relationship between the work motivation of nurses and the work productivity of nurses with p value = 0.063. There is no relationship between income level and work productivity with p value = 0.668. There is no relationship between work environment and work productivity with p value = 0.054. Conclusion There is no relationship between work motivation, income level, and work environment with work productivity in hospitals. Bhayangkara Tk III Manado.